Joint-dependence of strength and power in children and adults. - Denis, R. (University of Brunel, Centre for Sports Medicine and Human Performance, 2008)
The mechanisms underlying age-related differences in maximum power production during multi-joint exercises are not fully understood. Strength and power differences between children and adults cannot be solely explained by differences in muscle size. One factor that could potentially contribute to the age-related differences in maximum power production during multi-joint exercises is a differential development of the ability to generate maximum strength and power across the involved joints. Therefore, the purpose of this study was to investigate the age-related changes in strength and maximum power at the ankle and knee joints. Electromyography of the Gastrocnemius Medialis (GM) and Vastus Lateralis (VL) muscles was recorded to test the hypothesis of muscle specificity in the levels of activation. Twenty male volunteers participated in the study. They were divided into two age groups: children (n = 10, 11.6 ± 0.8 yrs) and adults (n = 10, 27.7 ± 5 yrs). Maximal torques at 0, 30, 75 and 120 deg.s-1 were determined during concentric ankle plantarflexion and knee extension using a Biodex system 3 (Shirley, New York, USA). Using multivariate analyses of variance, significant age by joint interactions for both isometric peak torque and maximal instantaneous power (p < .05) were identified. This effect was most prominent under isometric conditions, while it was reduced under dynamic conditions. The age by joint interaction for the magnitude of muscle activity was non-significant (p > .05). These results do not suggest a muscle joint-specific development of the ability to recruit. However, it seems that age-related increases in muscle strength and power are joint specific. A possible explanation for the joint specific development of strength is a muscle specific development of muscle structure.